PENGARUH PERSEPSI HARGA, KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN - Yani, Ahmad; Khotimah, Khusnul; Fitria, Lailani; Syafwandi, Syafwandi (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract The influence of price perceptions, service quality and trust on customer loyalty is a scientific article on literature studies within the scope of the field of Marketing Management Science. The aim of this article is to build a hypothesis of influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method using the research library comes from e-books and open access e-journals. Qualitative descriptive analysis. The results of this article: 1) Price perception influences customer loyalty; 2) Service quality influences customer loyalty; and 3) Trust influences customer loyalty. Keyword: Price Perception, Service Quality, Trust, Customer Loyalty